Impactos ambientales sobre el recurso hídrico producidos por la minería de carbón en Colombia, una revisión bibliográfica (2023)
Coal mining in Colombia has generated positive economic impacts, such as contribution to the national PIB, exports, royalty payments, employment generation and contribution to the country's energy supply, however, it is also mentioned that the excessive practice of coal mining has triggered negative environmental impacts on soil, air, flora, fauna and water resources, being originated by the bad practices of this industry and aggravated by legal and informal mining. The bibliographic review covers topics on the environmental impacts produced by coal mining in Colombia on water resources. The methodology used was qualitative, with the help of analysis, synthesis of information and data, using tools for data collection. By means of a rigorous search of information in scientific databases, 123 articles were identified and evaluated by means of software for later use in the execution of the project, implementing the use of the digital tool Parsifal to perform a systematic review of the bibliography found, which allowed synthesizing and selecting the information in less time. The objective of this bibliographic review is to present in a clear and synthesized manner the environmental impacts produced by coal mining in Colombia. As for the results, it was found that coal mining in Colombia has a significant impact on water resources, causing a decrease in the quality and quantity of water, which affects the fauna and flora of the area. In addition, several measures were identified to reduce the negative effects of coal mining on water resources, such as the implementation of cleaner technologies and the creation of environmental management plans.